Treatment of urinary disorders in patients with multiple sclerosis: A review - Igor V. Kuzmin; Svetlana V. Kuzmina (ZAO "Consilium Medicum", 2024)
Voiding disorders are one of the most common clinical manifestations of multiple sclerosis, significantly worsening the quality of life of patients. The review article provides information about the nature and symptoms of lower urinary tract dysfunctions, the reasons for their development and possible complications. The general principles of treatment of urinary disorders in patients with multiple sclerosis are presented, as well as features of the treatment of detrusor overactivity, detrusor-sphincter dyssynergia and detrusor hypoactivity. The possibilities of non-drug and drug therapy, botulinum therapy, and neuromodulation are described in detail. The role of intermittent catheterization in the treatment of patients with impaired evacuation function of the bladder is shown. Practical issues of choosing a treatment method depending on the clinical situation are considered.